Decision-Making Support of Truck Selection: A Systematic Review - Liandra Dos Santos Jesus; Gislaine Camila Lapasini Leal; Edwin Vladimir Cardoza Galdamez; Francisco Rodrigues Lima Junior (Dyna, 2020)
Trucks are attached to many industries in different sectors like an industrial equipment. For this reason, select a truck without consider the best attributes for the company could cause futures problems. Therefore, this article presents a systematic review of studies that approach quantitative and qualitative decision-making support methods and attributes that help on collecting of precision data. Thus, a framework was created to describe the factors and characteristics of studies, like the application types, hybrid models, sources and data validation. As result, 11 articles were selected from 893, published in English. And from the accepted articles valuation, multicriteria methods and a quality tool were found both applicated in decision-making support. Also, all the criteria, sub-criteria and attributes applicated by all the 11 authors in the methods were presented in this article and they were classified in 12 factors to simplify them.